Prediction of non financial firms merger and acquisition : an empirical study of Malaysian firms / Sin Boon Jiuan, Jane - Sin, Jane Boon Jiuan (2011)
In today’s competitive and globalized market, merger and acquisition (M&A) has become a strategy for the company to gain competitive advantage by expanding the pie (market share), entering new market, exploiting economies of scale, diversifying business risk and so on. This study has aimed to analyze the financial characteristics of the non financial merger and acquisition firms that had taken place from 2000 to 2008. The explanatory variables of this study were taken to signify profitability, liquidity, size and capital structure of the firms. Results of the t-test show that only firms’ size can be used to differentiate between the acquirers and target firms. The result of the logit analysis shows that only price earnings ratio support it hypothesis while profitability and capital structure proxy variables are partially supported in predicting the likelihood of the firms to become the target firms